Penerapan Al-Manhajul Khofiy (Hidden Curriculum) Pendidikan Agama Islam di MTs Nurul Quran Jogoroto Jombang - Basuni; Abdul Rouf; Dian Triana (FAI- Undar, 2018)
Education is essentially a transformation that converts inputs into outputs, in this transformation a process is needed that takes place correctly, is maintained, and requires regular training to be in accordance with educational goals. In life in the madrasa and the family is a miniature in the life of the nation/state. To realize a religious community culture, there is one madrasa that applies a hidden curriculum where the curriculum does not include the curriculum set by the government through the Minister of Education. So the authors are interested in researching even though it is simple, the extent of its influence on student behavior, both to friends, teachers and the environment (society) and what is the impact for students on the learning provided by the teacher. In this study, the author uses a qualitative descriptive approach, namely in the form of a comprehensive description and description of the actual situation. The research was conducted at MTs Nurul Qur'an Bendung Rejo Jogoroto. The reason why the researcher chose the Madrasah was because it was in the Madrasah that the curriculum was implemented. The forms of implementation of the Hidden Curriculum are: First, which are routine, namely: Morning prayer together, istighathah, Duha prayer and Dhuhur prayer in congregation, mushofahah and infaq and habituation of 4S (smile-greeting-greeting-polite). Second, which is incidental istighosah & religious tourism ahead of the National Examination, visits to sick friends and ta'ziah, religious social activities. Reading istighotsah which is a routine practice can make children obedient, polite, and delinquency is reduced drastically. The dluha prayer felt by respondents towards students, on average they grew more pious, disciplined and clean/holy so that it was easy to accept and understand the lessons delivered by the teacher, also with mushofahah it turned out that students had respect and tawadlu 'to the teacher. Based on the facts, the writer also found that there were students who still needed to be specially trained, and that was done. Thus, thank God the student can change and become better.